Antiretroviral treatment outcomes among late HIV presenters initiating treatment with integrase inhibitors or protease inhibitors. Issue 1 (13th October 2020) - Schuettfort, G; Boekenkamp, L; Cabello, A; Cotter, AG; De Leuw, P; Doctor, J; Górgolas, M; Hamzah, L; Herrmann, E; Kann, G; Khaykin, P; Mallon, PW; et al.
Abstract : Objectives: The aim of the study was to investigate the efficacy and safety of first‐line antiretroviral therapy (ART) with integrase inhibitor (INI) or protease inhibitor (PI)‐based regimens in patients with low CD4 cell counts and/or an AIDS‐defining disease. Methods: We conducted a retrospective, multicentre analysis to investigate discontinuation proportions and virological response in patients with CD4 cell counts < 200 cells/µL and/or AIDS‐defining disease when starting first‐line ART. Proportions of those discontinuing ART were compared using univariate analysis. Virological response was analysed using the Food & Drug Administration (FDA) snapshot analysis (HIV‐1 RNA < 50 HIV‐1 RNA copies/mL at week 48). Results: Two hundred and eighteen late presenters were included in the study: 13.8% were women and 23.8% were of non‐European ethnicity, and the mean baseline CD4 count was 91 cells/µL (standard deviation 112 cells/µL). A total of 131 late presenters started on INI‐ and 87 on PI‐based treatment. It was found that 86.1% of patients treated with INIs and 81.1% of patients treated with PIs had a viral load < 50 copies/mL at week 48; proportions of discontinuation because of adverse events were 6.1% in the INI group and 11.5% in the PI group. No significant differences in discontinuation proportions were observed at week 12 or 48 between INI‐ and PI‐based regimens ( P  = 0.76 and 0.52, respectively). Virological response was equally good in those receiving INIs and those receiving PIs (86.1% vs . 81.1%, respectively; P  = 0.36). Conclusions: In a European cohort of late presenters starting first‐line INI or PI‐based ART regimens, there were no significant differences in discontinuation proportions or virological response at week 48.